PS-039 DokuPIK – Pharmaceutical interventions: Do ward pharmacists know how to document?. (24th February 2014) - Ihbe-Heffinger, A; Langebrake, C; Leichenberg, K; Hilgarth, H; Hohmann, C; Kunkel, M; Lueb, M; Schuster, T
Abstract : Background: The internet-based categorical, hierarchical documentation system for routine pharmaceutical interventions (PIs) DokuPIK is widely used especially among German ward-based pharmacists. Purpose: To conduct a survey-based study on its clinical usability. Materials and methods: Out of 498 registered DokuPIK users, 37 volunteered to independently evaluate 24 standardised case reports 1 between 01–03 2012. Case evaluation was restricted to the reason for PI and was performed based on 26 given survey items with no limit on the number of items chosen. Ratings were conducted electronically and anonymously. In order to define meaningful reference item selections, majority decisions made by 5 senior clinical pharmacists were considered to be the gold standard. Agreement of raters' case evaluations with the gold standard was assessed by calculating the proportion of false positive and false negative answers, sensitivity, specificity, positive and negative predictive value (PPV - NPV) and was reported as median and range. Results: Independent assessment yielded a median agreement of 90% [79%–94%]. False positive ratings were not assessed as they only constituted 1% [0–2%]. False negative evaluations were revealed to be 10% [4–20%]. Sensitivity and specificity were 37% [21–57%] and 99% [97–100%] respectively. Median PPV and NPV were both 90% [60–100%] [78–95%]. Judging by the percentage variations from the judges' opinions, fp rate, specificity and NPV seem to be more robust than fn rate, sensitivity and PPV. Conclusions: Although comparable data are missing DokuPIKseems to have a favourable PPV and NPV and agree with the majority vote of senior clinical pharmacists. Despite the allowance of multiple choices, predictive values were good and indicate ﻿a well-considered decision. The low sensitivity, acceptable for an exclusively informative tool, is explained by a generally conservative attitude to recommending more than one possible intervention option by a single pharmacist whereas the reference definition relied on a majority decision. The variability among case reports should be further explored by subgroup analyses. Reference: Ganso 2007 KHP 28:279 No conflict of interest.